Effect of Temperature, Storage Time, The Residual Test of Neem Oil Formulation (Azadirachta indica A. JUSS) and Bitung Formulation (Baringtonia asiatica) to Its Toxicity Against Large Cabbage Heart Caterpillar (Crocidolomia pavonana F) - Neneng Sri Widayani; Afifah Nashirotul Haq; Lindung Tri Puspasari; Yusup Hidayat; Danar Dono (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2018)
Effectiveness of pesticide affected by many factors such as physical environment and duration of storage. This study aims to determine the effect of temperature and storage time of formulation of neem 50 EC and residual effect of formulation of neem 50 EC and formulation of bitung 30 SC against C. pavonana larvae. The formulations tested on the experiment of effect storage time and temperature test using the newly prepared, neem formulation has been stored for 19 months at room temperature 24.6-31.7oC, and stored in low temperature (4oC) as well as controls. The toxicity of the neem oil formulation was tested at concentrations of 1%, 2%, and 3%. The experiment of residual effect was performed by spraying of the formulation on broccoli leaf, then the leaf samples were taken on days 0,1,2,3,5,7,9,11, and 13 days after application of insecticide. The results of the research indicated that storage at low temperatures (temperature 4oC) for 19 months can maintain the toxicity of the neem formulation to C. pavonana larvae. while storage at room temperature for 19 months resulted in a decreased toxicity. The residual activity of the neem formulations at concentration of 0.8% and 2.4% were not caused mortality of C. pavonana larvae at the residual age of 13.34 days and 14.66 days. The activity of Bitung formulation at concentration of 1.1% and 2.8% were not caused mortality of C. pavonana larvae at the residual age of 11.33 days and 16.26 days.